2012
DOI: 10.1007/s10689-012-9556-0
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for breast cancer susceptibility associated with variants of BRD7, a component of p53 and BRCA1 pathways

Abstract: BRD7 (bromodomain 7), a subunit of poly-bromo-associated BRG1-associated factor (PBAF)-specific Swi/Snf chromatin remodeling complexes, has been proposed as a tumour suppressor protein following its identification as an important component of both functional p53 and BRCA1 (breast cancer 1, early onset) pathways. As low BRD7 expression levels have been linked to p53-wild-type breast tumour cells, we hypothesized an implication of BRD7 germline alterations in the pathogenesis of hereditary breast cancer similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…BRD7 regulates signaling pathways that involve cell growth, apoptosis, cell cycle, and mobility [14][15][16][17][18][19][20][21]. As a component of SWI/SNF chromatin-remodeling complexes, BRD7 interacts with other transcriptional factors, such as BRD2 [15], BRCA1 [22], and p53 [16], and transcriptionally regulates their target genes and downstream signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BRD7 regulates signaling pathways that involve cell growth, apoptosis, cell cycle, and mobility [14][15][16][17][18][19][20][21]. As a component of SWI/SNF chromatin-remodeling complexes, BRD7 interacts with other transcriptional factors, such as BRD2 [15], BRCA1 [22], and p53 [16], and transcriptionally regulates their target genes and downstream signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…BRD7 can inhibit cell growth through multiple mechanisms, including cell cycle arrest and apoptosis [14,15]. Recent work suggests that BRD7 acts as a transcriptional cofactor binding to BRCA-1 and p53 and is essential for the transcriptional activation of p53 target genes such as p21, MDM2, and TIGAR [16][17][18]. BRD7 is also a subunit of the SWI/SNF complex specific for polybromo BRG1-associated factor (PBAF) [19], modulates chromatin Electronic supplementary material The online version of this article (doi:10.1007/s11010-015-2568-y) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, it was found that BRD7 mutations represent rare polymorphisms in breast cancer, with no pathogenic effect. 17 MicroRNA-200c (miR-200c), which is over-expressed in endometrial carcinoma, inhibits BRD7 expression. 18 With little known about the molecular function of BRD7, and even less in the case of BRD9, potent and selective small molecule inhibitors would be valuable tools to study the roles of these proteins in transcription, elucidate their roles in oncology and other human diseases, and to test them as drug targets.…”
mentioning
confidence: 99%
“…In breast cancer, BRD7 was downregulated and even deleted on chromosome 16q12, in p53-wild-type but not mutant breast cancer cells [12]. Other studies proved that BRD7 was not a frequent high-penetrance susceptibility gene in breast cancer because its variants represented only rare polymorphisms [21] and no pathogenic BRD7 germ-line mutations were found in Triple Negative Breast Cancer patients with familial bC, ruling out the role of BRD7 in the genetic predisposition to breast cancer [22].…”
Section: Introductionmentioning
confidence: 99%